2017
DOI: 10.1111/jdv.14686
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional epidemiological study of hidradenitis suppurativa in an Irish population (SHIP)

Abstract: BackgroundHidradenitis suppurativa (HS), a chronic inflammatory disease that affects apocrine gland–bearing skin, has a significant impact on patients' quality of life. Estimates of the epidemiologic prevalence of HS are highly variable, and clinical data on disease characteristics and patient burden of disease remain limited.ObjectiveThe primary objective of this study was to determine the number of patients with HS attending dermatology clinics in a hospital setting in Ireland (within a 6‐month time period).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 23 publications
2
53
2
12
Order By: Relevance
“…There was no significant correlation between resilience and HRQoL in HS patients from the United States and Denmark . Profound impact on the HRQoL of Irish HS patients was reported, including diminished work productivity and various psychological comorbidities . The severity of odour in HS patients was associated with total Skindex‐29 scores but not with DLQI scores .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant correlation between resilience and HRQoL in HS patients from the United States and Denmark . Profound impact on the HRQoL of Irish HS patients was reported, including diminished work productivity and various psychological comorbidities . The severity of odour in HS patients was associated with total Skindex‐29 scores but not with DLQI scores .…”
Section: Resultsmentioning
confidence: 99%
“…82 Profound impact on the HRQoL of Irish HS patients was reported, including diminished work productivity and various psychological comorbidities. 83 The severity of odour in HS patients was associated with total Skindex-29 scores but not with DLQI scores. 84 In an international study of the QoL impact of treatment (the last DLQI item), over half of HS patients reported problems.…”
Section: Validation Of Hs-specific Qol Instrumentsmentioning
confidence: 88%
“…Dear Editor , Hidradenitis suppurativa (HS) is a chronic incurable disease of apocrine gland‐bearing skin characterized by double comedones, painful nodules and scarring most commonly in the axillae, inguinal and inframammary folds. Patients have increased rates of depression and anxiety and tend to come from lower socioeconomic backgrounds . Currently, recommended treatments include tetracycline antibiotics, rifampicin and clindamycin, acitretin, dapsone and biologic agents, including adalimumab and infliximab .…”
Section: Alternative Therapies Reported and Reasons For Use (N = 21)mentioning
confidence: 99%
“…These 12 studies comprised a combined study population of 53,794,009 across 9 different countries. Eleven studies [19][20][21][22][23][24][25][26][27][28]30 reported the prevalence and three studies reported the incidence. 23,24,29 Most studies examined patients of all ages.…”
Section: Study Selectionmentioning
confidence: 99%